Influence of Availability of Instructional Resources on learning Mathematics in North-western Nigeria - Musa Sirajo; Umar Abdullahi (Journal of General Education and Humanities, 2023)
This study used a comprehensive literature review to investigate the influence of the availability of instructional resources on learning mathematics in north-western Nigeria. It was performed by reviewing relevant books, articles, and journals. The study results show that a student's capacity to learn mathematics depends on the availability and utilization of instructional resources. Students' senses are stimulated, and the availability and use of instructional resources arouse their interest in the subject. When the applications of instructional resources are emphasized in schools, students perform better in mathematics. Instructional resources constitute a potent factor influencing the teaching and learning of mathematics in schools. The study recommends, among other things, that teachers should always use instructional materials during instruction in the classroom to enhance the student’s achievement in the subject.